The Effect of Market Concentration of Auditors and Tenure Audits on Audit Quality in Technology Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 Period - Melisa Putri Sagita Haris; Siti Nur Azijah Fatmi (Green Publisher Indonesia, 2026)
This study examines the impact of auditor market concentration and audit tenure on audit quality within technology firms listed on the Indonesia Stock Exchange (2022-2024). Using purposive sampling and panel data regression, audit quality is proxied via audit opinion. Findings reveal that high market concentration and extended audit tenure significantly reduce audit quality. These results suggest that oligopolistic structures and familiarity threats diminish professional skepticism. It is recommended to strengthen auditor rotation regulations and market competition oversight to ensure financial reporting integrity in digital-based sectors.